THE PHENOMENON OF CIVIC ENGAGEMENT AND ITS IMPACT ON THE CAPACITY OF LOCAL COMMUNITIES - Voznyi S.O. (Pressing Problems of Public Administration, 2016)
The article analyses theoretical approaches to de ning the phenomenon of civil activity in contemporarydemocratic society. They stressed the importance of the development of civic education in the processof local self-government reform. Conceptual directions of civil activity development in modern Ukrainewere proposed.